Follicular diameter range based on morphological features in Synbranchus marmoratus (Bloch, 1795) (Teleostei, Synbranchiformes, Synbranchidae) from the South-central region of Brazil - Spadella, M. A.; de Castilho-Almeida, R. B.; Quagio-Grassiotto, I; Cesario, Maria Dalva [UNESP] (Churchill Livingstone, 2005)
The morphological characteristics of Synbranchus marmoratus female germ cells in various development stages were described in details; then measurements of ovarian follicle diameters were taken from primary and secondary growth as during these development stages the oocyte size varied considerably along the fish growth. The results were correlated to total fish length, using the individuals division in six size classes. It was possible to group oocytes by stages according to histological characteristics but not according to morphometric diameter, as there was a wide variation in diameter in each stage and overlap between different maturation stages. These data make available new information on the reproductive biology of Synbranchidae. (c) 2004 Published by Elsevier Ltd.
Keywords: teleost fish; morphometry; folliculogenesis; oocytes; morphology